Peculiariaties of Achilles tendon liquid certain components changes determinated biochemically - Povstyanyi, V. A.; Pesotskaya, L. A.; Yevdokimenko, N. M.; Vastyanova, Ye. V.; Ostapenko, I. O. (Journal of Education, Health and Sport, 2017)
The work was investigated the kinetics of the changes components in the liquid that occur in the tissue of the Achilles tendon as a result of processes of autolysis, within 2-3, 4-6, 7-9 and 10-20 days post-mortem period. The calculation of the median values of the results obtained and the ratio of the current values of the median to the median of a very early period after death. Revealed the oscillatory nature of the change of components content of liquid in all later periods compared to the period of the death of 2-3 days. Proposed criteria for the analysis of the differences between the content of a number of compounds that are defined by biochemical and which may have a prognostic value to determine the time of death in late postmortem period (after 3 days).